Production of biosurfactants and bioemulsifiers by indigenous bacteria isolated from petroleum sludge and their association with total petroleum hydrocarbon degradation - Yusof, Nur Amira; Annuar, Nadhrah; Mohd Ashaari, Mardiana (2019)
Microbial biosurfactants and bioemulsifiers are amphiphilic, surface-active compounds produced during biodegradation, increasing the bioavailability of organic pollutants such as hydrocarbons. Both are known to be produced by bacteria to facilitate the process of hydrocarbon degradation and at the same time enhancing oil recovery in petroleum industry. Therefore, the existence of indigenous microorganisms that have the ability to consume petroleum hydrocarbon as carbon source and simultaneously produce biosurfactants and bioemulsifiers in order to facilitate hydrocarbon metabolism can be manipulated for bioremediation purposes. This study aimed to determine the association between the ability of indigenous bacteria isolated from petroleum sludge to produce biosurfactants and bioemulsifiers with their ability to degrade total petroleum hydrocarbons (TPH). Preliminary screenings of biosurfactant (i.e surface tension measurement) and bioemulsifier activity (i.e emulsification assay) from the total number of 26 isolates revealed some potential biosurfactant-producing bacteria (BSP) while some were potentially bioemulsifier-producing bacteria (BEP). Highest emulsification index (E24) exhibited by potential BEP (≈ 72.81 %) while for the rest of the isolates were between 64 to 68 %. Surface tension measurement revealed the biosurfactant activity of the isolates, which were as low as ≈ 18.92 mN/m for a potential BSP; while the rest were between the range of 45 to 28 mN/m. Two of these bacterial isolates (one potential BSP and one potential BEP) were further investigated for TPH biodegradation study using GC-MS. Assuming growth-linked biodegradation; growth curves of these bacterial isolates showed acclimation period for up to more than 72 hours of incubation; whereby no evident disappearance of TPH had been detected. However, after six days, rate of TPH loss became rapid; whereby biodegradation percentage of TPH was about (≈ 73 %). By the twelfth day of biodegradation study, the percentage of TPH loss was up to (≈ 85 %). In conclusion, both potential BSP and BEP were potent hydrocarbon biodegraders and that both biosurfactants and bioemulsifiers were unique microbial products showing advantageous features in hydrocarbon biodegradation. Both bioemulsifiers and biosurfactants could be extracted and purified from bacteria as both molecules have great potential for application in green technology.